NATIONAL INSIGHTS FROM LITHUANIA, LATVIA AND POLAND FOR EU ADULT EDUCATION POLICY DEVELOPMENT - Melnikova, Julija; Ahrens, Andreas; Zaščerinska, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The discovery of the power of adult education in facilitating smart, sustainable and inclusive growth has increased the demand for adult learning. Education in European countries had always been seen as a national affair. The education systems and objectives had been closely related with each country’s history, political system and location. However, due to the increasingly global character of the way national and supranational policy is created, education policymaking is increasingly framed by national economic imperatives and driven by the need to be globally competitive. The education of adults is a component of these politics, and has become a powerful lever for shifting the boundaries between education and work, state and market, formal and informal education. The aim of the present article is to highlight the national perspectives of Lithuania and such neighbourhood countries as Latvia, Estonia and Poland. Despite national diversities, a cursory glance at contemporary processes in adult education across European states brings to light many common or similar characteristics in systems and mechanisms. Moreover, comparative perspective of countries’ experience and expertise is beneficial for improving of the quality of adult education. The novel contribution of the work is revealed in recommendations on policy for adult learning.